1991
DOI: 10.1002/j.1537-2197.1991.tb15202.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Rna Synthesis in the Shoot Apex of Pharbitis Nil During Floral Evocation

Abstract: Early events in the evocation of the flower in Pharbitis nil Chois seedlings were investigated by following the incorporation of tritiated uridine into the shoot apex. The uridine was applied to the expanded cotyledons of seedlings at 8 hr into the inductive dark period. The shoot tips were fixed at 20 hr (a 12-hr labeling period). After the 12-hr labeling period there was considerable label throughout the shoot tips of both control plants (dark period interrupted with 5 min of red light at 8 hr) and plants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
1994
1994

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The pattern of CDCP expression appears to be modified during the I -, F transition. High levels of CDC2 transcript in the rib meristem and developing pedicel may reflect the increased mitotic and metabolic activity in this region during floral meristem initiation (Vaughn, 1955;Wetmore et al, 1959;Bonner et al, 1991). Martinez et al (1992) also noted that the expression pattern of CDC2 in the early floral meristem is the reciproca1 of the pattern displayed by several of the floral homeotic genes, and they suggested that antagonistic interactions between CDC2 and the homeotic genes may determine these expression patterns.…”
Section: Evidence For Modlfled Patterns Of Meristem Gene Expression During the Vegetative-to-floral Transltlonmentioning
confidence: 99%
“…The pattern of CDCP expression appears to be modified during the I -, F transition. High levels of CDC2 transcript in the rib meristem and developing pedicel may reflect the increased mitotic and metabolic activity in this region during floral meristem initiation (Vaughn, 1955;Wetmore et al, 1959;Bonner et al, 1991). Martinez et al (1992) also noted that the expression pattern of CDC2 in the early floral meristem is the reciproca1 of the pattern displayed by several of the floral homeotic genes, and they suggested that antagonistic interactions between CDC2 and the homeotic genes may determine these expression patterns.…”
Section: Evidence For Modlfled Patterns Of Meristem Gene Expression During the Vegetative-to-floral Transltlonmentioning
confidence: 99%
“…Another example is provided by the study of Melzer et al (1990), in which a number of genes whose transcripts are up-regulated during floral transition in mustard were found to show high levels of mRNA at the base of the meristem and pedicel. Furthermore, Bonner et al (1991) reported an increased synthesis of RNA at the base of the meristem of Pharbitis nil following the induction of flowering. Even earlier studies (e.g., Gifford and Tepper, 1962;Marc and Palmer, 1982) have suggested that a relative metabolic activation of the lower, interna1 cells of the meristem is a significant occurrence within the meristem during floral transition.…”
Section: Activation Of Basal Cells Of the Floral Meristem May Be A Gementioning
confidence: 99%